INNOVATION FOR A SUSTAINABLE BUILT ENVIRONMENT - Emilia L.C. van de Wilde de Ligny Egmond (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
Despite the indisputable contribution of innovations to socio-economic development, the world has realized that many innovations and technologies have been a major cause of climatic change and resource depletion. This research aimed to identify how and whether innovation in construction contributes to achieve a sustainable built environment. An analytical framework -derived from literature studies on evidence and theories on innovation in manufacturing-was applied in Dutch construction. The study underpinned that sustainable construction requires innovative solutions which go beyond the traditional and generally accepted way of building. Government support appeared necessary for a regime shift to stimulate innovation for a sustainable built environment. Policies thus should be directed to tackle a major bottleneck in construction: knowledge, expectations and beliefs concerning innovation for sustainable construction.